Variability and climate change in the Mantaro river basin, central Peruvian Andes - Silva Vidal, Yamina (2006)
The present work is part of the "Integrated Local Assessment of the Mantaro River Basin" (ILA Mantaro), whose main objective was: to systematize and to extend the knowledge about climate change in the Mantaro river basin, and to evaluate the climatic, physical and social aspects of its vulnerability, as well as to identify viable adaptation options for the agriculture, hydroelectric energy and health sectors, to be incorporated into local and regional development planning. In this context, the climatic component of the study consisted in the analysis of the climatic characteristics of the river basin: intraseasonal and interannual variability of rainfall over the basin, the relation of regional climate with atmospheric patterns on regional and global scale, the climatic trends in the last 50 or 40 years, and the characteristics of the freezes and the trends in their frequency and intensity. On the other hand, the generation of future climatic scenarios for the river basin, constituted one of the most important objectives. These results were used for the analysis of the present and future vulnerability in the Mantaro river basin to climate variability and change, as well as for the proposal of adaptation measures.